Technical and scientific terms in poetry translation: The tensions of an 'anti-poetical' textual feature - Feng Wang; Kelly Washbourne (JoSTrans: The Journal of Specialised Translation)
Technicisms in poetry constitute a close relative to allusions but can be functionally different, as technicisms may or may not have allusive force. Metaphor occurring in science, and science employed in poetry, show that science and art are two sides of the same coin, rather than vastly different orders of experience. We propose, then, the hybrid literary-technical translation in this study to refer to those textual nodes where the translator must contend strategically with scientific realities. After establishing the ongoing 'two cultures' divide, we explore the premise that the problem of literariness includes literary terminology, which often lies at the crossroads of aesthetic and technical priorities, or appearance versus function. We attend to problems and solutions of literary technicality, including neology, culture-specificity, and unscientific ('ornamental') science, and conclude that these phenomena complicate the translator's position between referring and naming, terminologising and determinologising. Our contentions apply particularly to poetry, especially classical poetry. We engage examples from Chinese into English.